Nursing interventions in the management program for chronic patients: cross mapping - Talita do Nascimento da Silva; Rosimere Ferreira Santana; George Luiz Alves Santos; Luana de França da Silva; Giselle Mota Bastos; Thaís Diniz Garcia (Rev Rene)
One aimed to analyze nursing interventions in the medical records of the elderly assisted by the management program for chronic patients, comparing them with the Nursing Interventions Classification. The investigation was carried out in a private health service in Rio de Janeiro, Brazil, in March 2014. This is a cross mapping study, with a quantitative approach. The sample was composed of 80 medical records according to the following criteria: attended in 2013; average complexity II; age over 64 years old; received more than five home visits; and being active on December 2013 in low complexity I. The frequently mapped interventions were: education – disease process (98%); nutritional counseling (98%); environment control (95%); and exercise promotion (94%). The decline in the functional status of the program indicates that the guidelines were effective, but they are not standardized yet. It is recommended the adoption of a standardized language.